"Blodet suser". Melodrama og emotioner i Herman Bangs "De fire djævle" - Heitmann, Annegret (K&K - Kultur og Klasse, 2011)
“THE BLOOD RUSHES”. MELODRAMA AND EMOTIONS IN HERMAN BANG’S “DE FIRE DJÆVLE” Starting from the melodramatic quality of some of Herman Bang’s texts, the article tries to show its specific function through a reading of “De fire Djævle”. Applying some thoughts of current research on affectivity, it links the narrative expressions of strong emotions to contemporary discourses on trauma on the one hand, and energy and entropy on the other. Affects are shown to be unreliable signs of complex or even repressed phenomena; the story therefore advocates scepticism regarding language, which has an analogy in the silence of the four artistes. Their trapeze-act can be read as a poetological signal for the story itself: dramatic feelings issue from a self-discipline that withholds its repressed motivation.